Clinical Characteristics and Outcomes of Severe and Critical Patients With 2019 Novel Coronavirus Disease (COVID-19) in Wenzhou: A Retrospective Study - Qian, Song-Zan; Hong, Wan-dong; Lingjie-mao,; Chenfeng-lin,; Zhendong-fang,; Pan, Jing-Ye (Frontiers in Medicine, 2020)
Information about severe cases with 2019 novel coronavirus disease (COVID-19) infection is scarce. The aim of this study was to report the clinical characteristics and outcomes of severe and critical patients with confirmed COVID-19 infection in Wenzhou city. In this single-centered, retrospective cohort study, we consecutively enrolled 37 RT-PCR confirmed positive severe or critical patients from January 28th to February 16th, 2020 in a tertiary hospital. Outcomes were followed up until 28-day mortality. 15 Severe and 22 critical adult patients with COVID-19 infection were included. 26(68.4%）were men. Echocardiography data results suggest that normal or increased cardiac output and diastolic dysfunction are the most common manifestations. Compared with severe patient, critical patient were older, more likely with low platelet counts and high blood urea nitrogen, longer in-hospital days. Most patients had organ dysfunction during hospitalization, including 11 (29.7%) with ARDS, 8(21.6%) with acute kidney injury, 17(45.9%) with acute cardiac injury, 33 (89.2%) with acute liver dysfunction. 18(48.6%) patients were treated with high-flow ventilation, 9 (13.8%) with noninvasive ventilation, 10(15.4%) with invasive mechanical ventilation, 7 (18.9%) with prone position ventilation, 6 (16.2%) with extracorporeal membrane oxygenation (ECMO), 3 (8.1%) with renal replacement therapy. Only 1 (2.7%) patients had died in 28-day fellow up in our study. All patients had bilateral infiltrates on chest CT scan. 21(32.3%) patients presented ground glass opacity (GGO) and critical patients more localized in the periphery and the center. The mortality of critical patients with COVID-19 infection is low in our study. Cardiac function was enhanced in early stage and less likely to develop acute cardiac injury, but most of patient suffered with acute liver injury. The CT imaging presentations of COVID-19 in critical patient are more likely with consolidation and bilateral lung involvement.